University student and teacher perceptions of teacher roles in promoting autonomous language learning with technology outside the classroom. Issue 4 (18th May 2016) - Lai, Chun; Yeung, Yuk; Hu, Jingjing
Abstract : Helping students to become autonomous learners, who actively utilize technologies for learning outside the classroom, is important for successful language learning. Teachers, as significant social agents who shape students' intellectual and social experiences, have a critical role to play. This study examined students' and teachers' perceptions of the specific roles teachers may play in promoting autonomous language learning with technology outside the classroom. Interviews were conducted with 15 language learners and 10 language teachers at a university in Hong Kong. The study found mismatches between students' and teachers' perceptions of the degree of teacher involvement and the specific roles teachers could play. On the one hand, students expected teachers to play a greater role in supporting their autonomous learning with technology by recommending a variety of technological resources and sharing metacognitive and cognitive strategies for effective use of the resources. On the other hand, teachers expected to play a minimal role due to their overestimation of students' capacities and their concern over their limited abilities to provide such support. The research findings indicate the importance of raising teachers' awareness of the various roles their students expect them to play and of equipping teachers with the knowledge and skills to advise and support students in making use of technological resources outside the classroom for language learning.